Communications, Signal Processing, and Systems Proceedings of the 2016 International Conference on Communications, Signal Processing, and Systems (Lecture Notes in Electrical Engineering,, 2018)
This book brings together papers presented at the 2016 International Conference on Communications, Signal Processing, and Systems, which provides a venue to disseminate the latest developments and to discuss the interactions and links between these multidisciplinary fields. Spanning topics ranging from communications to signal processing and systems, this book is aimed at undergraduate and graduate students in electrical engineering, computer science and mathematics, researchers and engineers from academia and industry as well as government employees (such as NSF, DOD and DOE).